Economic Estimation of Project Risks when Exploring Sea Gas and Oil Deposits in the Russian Arctic - Nikulina, Anni Yulievna; Kruk, Marina Nikolayevna (International Journal of Economics and Financial Issues, 2016)
The aim of the article is to develop the methodology of economic estimation of risks when exploring shelf deposits of the Ob Bay in the Arctic Region of Russia. It considers various methods of accounting and economic estimation of risks: sensitivity analysis, scenarios method, imitation modeling, and the method of real options. Calculations and the conclusion about the most rational method for calculating sea Arctic projects were made. This method of real options allows to take into account peculiarities of venture projects. This work is practically important because the offered methodology can be applied for all gas-and-oil deposits at the Arctic shelf of Russia that have been actively developed over the last decade. Keywords: Risk, option, oil, gas, shelf, deposit, sensitivity analysis. JEL Classifications: Q32, Q39, Q47.